Toxoplasma gondii, Neospora caninum and Leishmania spp. serology and Leishmania spp. PCR in dogs from Pirassununga, SP - Nathália Mendonça de Seabra (Revista Brasileira de Parasitologia Veterinária)
Abstract We examined the presence of antibodies against the parasites Toxoplasma gondii, Neospora caninum, and Leishmania spp., as well the presence of DNA from Leishmania spp., in dogs from Pirassununga - SP. The seropositivity rate was compared with the animals’ originating location. Three hundred seventy-three blood samples from the county’s kennel and local veterinary clinics were collected and analyzed. A total of 300 samples were tested for T. gondii and N. caninum using an indirect immunofluorescence antibody test (IFAT); 45% (135/300) were positive for T. gondii and 24.3% (73/300) were positive for N. caninum. Three hundred seventy-three samples were tested for Leishmania spp. using the IFAT. Of these, 4.6% (17/373) were positive. Additionally, 145 samples were tested using a polymerase chain reaction (PCR); of these samples, 0.7% (1/145) was positive. Considering the results, we conclude that these parasites are present in the city of Pirassununga - SP and that the animals have contact with the protozoan. It is therefore necessary to create methods for disease prevention to maintain both animal and human health in regard to leishmaniasis and toxoplasmosis.